THU0148 COMPARISON OF SERUM LEVELS OF GDF-15 IN PATIENTS WITH RHEUMATOID ARTHRITIS WITH OR WITHOUT DISEASE ACTIVITY. (June 2019) - Mendoza-Vázquez, Guadalupe; Espinoza-Gómez, Francisco; Zavala, Maria; Guzmán-Silahua, Sandra; Riebeling-Navarro, Carlos; Nava-Zavala, Arnulfo Hernán
Abstract : Background: The increase in morbidity and mortality in Rheumatoid arthritis (RA) is due to 50% by cardiovascular risk factors associated with chronic-inflammatory processes, among these factors, GDF-15 has been associated with chronic-inflammatory processes such as RA; in addition to being related to the state of the disease of several pathologies with similar mechanisms. GDF-15 could be involved in the pathogenesis of RA and thus, show an association with the activity of a disease in RA. The most common clinimetric tool to evaluate disease activity in RA is Disease Activity Score on 28 joints (DAS28). Objectives: To compare the serum levels of GDF-15 in patients with RA with or without disease activity. Methods: Cross-sectional study, including 162 patients with RA, aged ≥18 years old who fulfilled the 1987 ACR classification criteria. RA disease activity was assessed using DAS28-PCR. Sera samples were obtained from venous blood by centrifugation at 3500 rpm for 15 min at room temperature. Serum GDF-15 was measured using an ELISA kit (BioVendor, Germany). Descriptive statistics (mean and standard deviation (SD)) were used for assessing the demographics and clinical parameters. Differences between patients with and without disease activity were assessed using T-student and Chi 2 tests. P-values ≤0.05 were considered statistically significant. Results: The mean age was 57.2 ± 11.5 years and mean BMI was 27.52 ± 4.78 kg/m 2 . The mean disease duration was 13.60 ± 9.50 years. The GDF-15 was 435.54 ± 310.64 ng/L. For number of swollen and tender joints, the score was 1.50 ± 3.52 and 2.81 ± 4.59 respectively. VAS-pain was 37.00 ± 27.77. DAS28-CRP score was 3.15 ± 1.18. When applying the cut-off value for disease activity (DAS28 score ≥2.6) or remission (DAS28 score <2.6) we obtained 65 (40.1%) and 97 (59.9%) respectively. Comparison of GDF-15 serum levels between active (455.09 ± 333.47) and remission (406.36 ± 272.94) showed no significant associations (p=0.32). When performing Pearson's correlation among GDF-15 serum levels and PCR levels (r=0.142, p=0.07) or DAS28-PCR values (r=0.081, p=0.30) no relevant correlations were obtained. Conclusion: RA activity is not associated with values of serum levels of GDF-15. Prospective studies are necessary to explain changes in GDF-15 levels throughout RA. References: [1] Wiklund FE, Bennet AM, Magnusson PK, Eriksson UK, Lindmark F, Wu L, Yaghoutyfam N, Marquis CP, Stattin P, Pedersen NL, Adami HO, Grönberg H, Breit SN, Brown DA. Macrophage inhibitory cytokine-1 (MIC-1/GDF15): a new marker of all-cause mortality. Aging Cell. 2010 Dec; 9(6):1057-64. [2] Brown DA, Moore J, Johnen H, Smeets TJ, Bauskin AR, Kuffner T, Weedon H, Milliken ST, Tak PP, Smith MD, Breit SN. Serum macrophage inhibitory cytokine 1 in rheumatoid arthritis: a potential marker of erosive joint destruction.Arthritis Rheum. 2007 Mar; 56(3):753-64. Disclosure of Interests: None declared